Histopathological Study of Some Tigris River Fish Which Infected by Parasites: Mansor, N.T.;* Falah, A.B.; Al- Jawda, J.M.; Asmar, K.R. - T., Mansor, N. (The Iraqi Journal of Veterinary Medicine, 2012)
A total of 69 fish samples were collected from three stations Tigris River namely (Al-Zaafaraniya, Al-Tagei and Al-Shawaka) at Baghdad city, during the period from January to December 2010). These fishes were belonging to five species which were Barbus luteus, Carassius carassius, Chondrostoma regium, Liza abu and Silurus triostegus. The microscopial examination revealed infection with 39 species of ectoparasites and endoparasites including twenty one from protozoans (five ciliate (E.cyprini, E.dogieli, E.spherica, T.domerguei, T.nigra) and sixteen sporozoa (C.bychowski, Myxidium monstrasum, M.pfeifferi, M.rhodei, Myxobolus bramae, M.cyprini, M.cyprinicola, M.drgajini, M.koi, M.macrocapsulari, M.mulleri, M.oviformis, M.paljanski, M.parvus, M.pfeifferi and M.spherica)),twelve trematodes (nine of them from Monogenea (A.siluri , D.achmerovi , D.anchoratus, D.dulkiti, D.formosus, D.skarjabini, D.varicohrini,D.vasator and Diplozoon pavloviski) three digenea(A.coleostoma,D.commutatum, D.spathacum)), one nematode Rabdicona sp., two acanthocephala (N.cristatus, N.iraqensis), two crustaceans (D.varicoleus, E.sieboldi) and one from fungus I.hoferi. The present study included the histopathological changes which caused by Myxobolus on the site of infection (muscles, kidneys and gills) included muscular disorganization, necrosis, bleeding, hemorrhage and mononuclear cells infiltration, hyperplasia and telengiectasis on the gills secondary lamella. Also, the present study included the histopathological changes on the intestine which infected with Neochinorhynchus iraqinesis included closed of intestinal lumen with parasites section, debris necrosis, severe reduce of intestinal filament and mononuclear cells infiltration.